Naringenin Protects HaCaT Human Keratinocytes Against UVB-induced Apoptosis and Enhances the Removal of Cyclobutane Pyrimidine Dimers from the Genome - El-Mahdy, Mohamed A.; Zhu, Qianzheng; Wang, Qi-En; Wani, Gulzar; Patnaik, Srinivas; Zhao, Qun; Arafa, El-Shaimaa; Barakat, Bassant; Mir, Safita N.; Wani, Altaf A. (Photochemistry and photobiology, 2008)
Many naturally occurring agents are believed to protect against UV‐induced skin damage. In this study, we have investigated the effects of naringenin (NG), a naturally occurring citrus flavonone, on the removal of UVB‐induced cyclobutane pyrimidine dimers (CPD) from the genome and apoptosis in immortalized p53‐mutant human keratinocyte HaCaT cells. The colony‐forming assay shows that treatment with NG significantly increases long‐term cell survival after UVB irradiation. NG treatment also protects the cells from UVB‐induced apoptosis, as indicated by the absence of the 180 base pair DNA ladders and the appearance of sub‐G1 peak using agarose gel electrophoresis and flow cytometric analysis, respectively. The UVB‐induced poly (ADP‐ribose) polymerase‐1 (PARP‐1) cleavage, caspase activation and Bax/Bcl2 ratio were modulated following NG treatment, indicating an antiapoptotic effect of NG in UVB‐damaged cells that occurs at least in part via caspase cascade pathway. Moreover, treatment of UVB‐irradiated HaCaT cells with NG enhances the removal of CPD from the genome, as observed by both direct quantitation of CPD in genomic DNA and immuno‐localization of the damage within the nuclei. The study provides a molecular basis for the action of NG as a promising natural flavonoid in preventing skin aging and carcinogenesis.